1992
DOI: 10.3758/bf03199667
|View full text |Cite
|
Sign up to set email alerts
|

Semantic priming in the pronunciation of words in two writing systems: Italian and English

Abstract: Semantic priming effects in naming Italian and English words were investigated. Experiments 1 and 2 were in Italian. In Experiment 1, the subjects named a target word, which was either associated with or unrelated to a preceding prime. The results showed semantic priming effects. However, in Experiment 2, in which the same materials occurred in a list that also included pseudowords, priming effects were obtained with the lexical decision task, but not with pronunciation. In Experiment 3, the inclusion of pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
141
5
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 49 publications
16
141
5
2
Order By: Relevance
“…These results have interesting implications for models of reading and lexical representation in Italian. The fact that subjects named highfrequency words faster than low-frequency words, even though Italian has a segmentally shallow orthography , is consistent with the view that under normal circumstances, oral reading in Italian is lexically mediated (Miceli & Caramazza, 1993;Tabossi & Laghi, 1992). 5,6 It is important to emphasise that even though Italian orthography is segmentally transparent, the correct pronunciation of words requires access to word-speci c knowledge because word stress is assigned lexically.…”
Section: Resultsmentioning
confidence: 59%
“…These results have interesting implications for models of reading and lexical representation in Italian. The fact that subjects named highfrequency words faster than low-frequency words, even though Italian has a segmentally shallow orthography , is consistent with the view that under normal circumstances, oral reading in Italian is lexically mediated (Miceli & Caramazza, 1993;Tabossi & Laghi, 1992). 5,6 It is important to emphasise that even though Italian orthography is segmentally transparent, the correct pronunciation of words requires access to word-speci c knowledge because word stress is assigned lexically.…”
Section: Resultsmentioning
confidence: 59%
“…This shows that the distinction between the two concepts is meaningful, as they are not perfectly correlated between orthographies. The Italian DRC shows an even smaller number of rules, and a larger proportion of singleletter rules, consistent with the notion that it is an extremely shallow orthography (e.g., Tabossi & Laghi, 1992).…”
mentioning
confidence: 49%
“…This suggests that the presence of orthographically deep words, which do not easily afford direct translation of spelling to sound, induces a greater reliance on frequency-sensitive, lexical-semantic processing. A similar experiment in Italian (Tabossi & Laghi, 1992) demonstrated that semantic priming effects in a naming task were diminished when nonwords were included in the stimulus list Interestingly, they failed to replicate this interaction in English with less regular stimuli. As noted above, results consistent with these findings have also been obtained in Farsi (Baluch & Besner, 1991) and in Turkish (Raman etal., 1996).…”
Section: Evidence For the Attentional Control Hypothesismentioning
confidence: 99%
“…Recently, there has been a good deal of debate as to whether skilled readers have attentional control over the degree to which lexical and sublexical information contribute to naming performance (Balota, Law, & Zevin, 1999;Balota, Paul, & Spieler, 1999;Baluch & Besner, 1991;Lupker, Brown, & Colombo, 1997;Jared, 1997;Monsell, Patterson, Graham, Hughes, & Milroy, 1992;Simpson & Kang, 1994;Tabossi & Laghi, 1992). Clearly, there are situations in which it might be desirable to attend selectively to one or another aspect of visually presented text.…”
mentioning
confidence: 99%